Entropy production during natural convection of hybrid nanofluid in an annular passage between horizontal confocal elliptic cylinders - Tayebi, Tahar; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2020)
A numerical analysis on entropy production due to natural convection in an annular passage between horizontal confocal elliptic cylinders is studied. The Al2O3-Cu/water hybrid nanofluid is using as a test fluid. The flow by natural convection in the annulus is driven by a gradient of temperature between an internal uniformly heated elliptical cylinder and a cold external elliptical cylinder. The full basic equations describing steady laminar flow of incompressible and Newtonian fluid under the Boussinesq approximation are expressed in the elliptical coordinates system and discretized by the finite volume method using an in-house FORTRAN code. The investigation is carried out to examine the influences of Rayleigh number and hybrid nanoparticles volume fraction on thermohydrodynamic characteristics, heat transfer and entropy generation inside the annulus. Obtained results showed that increase of Rayleigh number or use of hybrid nanoparticles in the pure water increases the natural convective flow and the heat transfer rate within the annulus, as well as both thermal and frictional entropy generation. Also, at lower Rayleigh, most of the entropy generation is due to the thermal irreversibility, whereas, at higher Rayleigh, the main contributor to the total entropy generation is that due to the frictional irreversibility.
Keywords: Entropy generation; Elliptical annulus; Natural convection; Hybrid nanofluid; Elliptical coordinates; Heat transfer